On Architecture as a Spatial Art - Sauchelli, Andrea (The Nordic Journal of Aesthetics, 2012)
I present and evaluate various criticisms against the view that architecture and architectural value are to be understood solely in terms of internal space. I conclude that the architectural value of a building should not be limited to its internal spatial effects because the value of other elements, such as (non-spatial) function, materials, ornamentation, and so on cannot all be reduced to spatial values.